The effects of low-pressure hyperbaric oxygen treatment before and after maximal exercise on lactate concentration, heart rate recovery, and antioxidant capacity - Park, Si-Hwa (J Exerc Rehabil, 2018)
The purpose of this study was to investigate the effects of low-pressure hyperbaric oxygen (HBO) treatment before and after maximal exercise on lactate concentration and heart rate and antioxidant capacity. Ten healthy male college students were recruited from amateur soccer players. Subjects were performed a maximal exercise 3 times at intervals of at least 7 days according to the treatment method (control, pretreatment, posttreatment). Lactate concentration, heart rate, and antioxidant capacity were measured before, post, and after recovery 30 min of maximal exercise. The lactate concentration and heart rate of recovery 30 min was significantly lower in the low-pressure HBO treated group after the maximal exercise compared with the control group and the low-pressure HBO treated group before maximal exercise, and it could affect the removal of the fatigue substance caused by the maximal exercise. These results suggest that the low-pressure HBO treatment which is a new possibility for recovery of peripheral fatigue.